Gotong Royong Implementasi Ekonomi Berkelanjutan dan Bermoral - Eunike Rose Mita Lukiani; Noer Aida Triandini (CV. ALIM'SPUBLISHING, 2026)
This article examines the concept of Gotong royong and its role as a foundation for a sustainable and ethical economy. The growing environmental challenges and the limitations of carbon-intensive economic systems highlight the need for a transition toward a green economy that balances economic development with social and environmental sustainability. This study employs the Systematic Review of the Literature (SRL) method by analyzing relevant academic publications on Gotong royong, local wisdom, and sustainable economic development. The findings reveal that Gotong royong represents an indigenous cultural value of Indonesia that reflects collective wisdom in managing economic resources through cooperation, mutual assistance, and shared responsibility. Beyond its economic function, Gotong royong contributes to character development by transforming negative traits such as selfishness, greed, envy, arrogance, and laziness into positive values including sincerity, patience, integrity, loyalty, responsibility, and willingness to sacrifice for the common good. The practice of Gotong royong also promotes harmonious relationships among humans, God, society, and nature, making it consistent with the principles of sustainable development and economic ethics. Therefore, Gotong royong can be regarded as an alternative paradigm for economic mechanisms that emphasize collaboration, moral responsibility, and environmental sustainability. This study contributes to the international discourse by demonstrating that Indonesia's local wisdom offers a relevant framework for developing a more sustainable, ethical, and inclusive economic system.